1976
DOI: 10.3406/psy.1976.28151
|View full text |Cite
|
Sign up to set email alerts
|

La perception du mouvement en profondeur chez le nourrisson

Abstract: Summary A looming paradigm was used to determine what depth information infants process in addition to that provided by the expansion of a single, closed contour of an object. A total of 33 infants aged 22 to 48 days watched a film in which the circular elements and inter-element spaces of the projected image alternately expanded and contracted. A display containing 800 black disks elicited significantly more head responses directed away from the screen than displays having either one or three disks of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sensitivity to these sources of information develops during the first months of life (for a review, see Kellman & Arterberry, 2006). Kinematic information is used as distance information by 1 month of age (e.g., Ball & Vurpillot, 1976; Náñez & Yonas, 1994); convergence is utilized as absolute distance information by 4–7 months of age (von Hofsten, 1977); and reactivity to binocular disparity emerges between 2 and 4 months of age, accompanied by the onset of stereoscopic depth perception (e.g., Brown & Miracle, 2003; Fox, Aslin, Shea, & Dumais, 1980; Granrud, 1986).…”
mentioning
confidence: 99%
“…Sensitivity to these sources of information develops during the first months of life (for a review, see Kellman & Arterberry, 2006). Kinematic information is used as distance information by 1 month of age (e.g., Ball & Vurpillot, 1976; Náñez & Yonas, 1994); convergence is utilized as absolute distance information by 4–7 months of age (von Hofsten, 1977); and reactivity to binocular disparity emerges between 2 and 4 months of age, accompanied by the onset of stereoscopic depth perception (e.g., Brown & Miracle, 2003; Fox, Aslin, Shea, & Dumais, 1980; Granrud, 1986).…”
mentioning
confidence: 99%
“…Keeping one's eyes open wide as an object approaches on a collision course hardly seems an adaptive defence; indeed, most of the previously published studies on the development of responsiveness to information for approach (cf., Peiper, 1963;Jones, 1926;White, 1971) have used the blink response -or closing the eyes -as the sole indicator of depth sensitivity. And emotional upset and crying might indicate that the infant is detecting a noxious event, but other experimenters have not found that the approach of an object evokes an emotional response (Ball & Tronick, 1971;Ball & Vurpillot, 1976;. Even backward head movements, reported to occur consistently when young infants are shown looming displays (Ball & Tronick, 1971;Ball & Vurpillot, 1976;Yonas etal., 1977), present a problem of interpretation.…”
mentioning
confidence: 99%
“…And emotional upset and crying might indicate that the infant is detecting a noxious event, but other experimenters have not found that the approach of an object evokes an emotional response (Ball & Tronick, 1971;Ball & Vurpillot, 1976;. Even backward head movements, reported to occur consistently when young infants are shown looming displays (Ball & Tronick, 1971;Ball & Vurpillot, 1976;Yonas etal., 1977), present a problem of interpretation. As Ball (Note 1) pointed out, the upward rotation of the infant's head may be attributed to tracking the upper contour of the display, rather than to a defensive reaction.…”
mentioning
confidence: 99%